利用非傳統穩定同位素探討前寒武紀/寒武紀過渡期之古環境變化(IV) - 游鎮烽 (2020)
計畫編號︰MOST109-2116-M006-010 執行機構: 國立成功大學地球科學系（所） 研究期間: 2020-08~2021-07 地球歷史與生命演化有著緊密的關聯性。地表環境變遷將導致適合者生存。遠古宙至早顯生宙地層，介於埃迪卡拉和寒武紀過渡帶岩層，記錄著雪球地球時期劇烈氣候、環境和生物演化資訊。為研究相關地層，我們組成國際研究團隊(中、台、蘇和美國)，進行合作研究，預期可產生整合資料，提供關於埃迪卡拉雪球地球和早期生命演化的相關過程。此團隊已利用雷射剝蝕及nanoSIMS進行定年，證實碎屑礦物對定年結果有關鍵影響。初步年代資料顯示詳細微區觀測是礦物標地定年重要前置工作；已有二篇相關文章收錄於2019 PC-C Phosphogenic Event ”前寒武紀研究”專刊(發表中)。此為延續性計畫第四年，我們已參與兩屆「寒武紀/前寒武紀過渡帶」於中國科技大學及美國UCLA舉辦聯合會議，並前往貴州省貴陽和甕安等地野外勘查，採得珍貴含磷標本，利用東京大學或地科所NanoSIMS，對磷灰石及磷釔礦、獨居石和鋯石進行微區U-Pb定年，目前已針對微區礦物中硫同位素、REEs及微量元素進行初步評估，並部分完成XRF、XRD和拉曼光譜等觀察；109年將挑選重要碳酸鹽或磷酸鹽樣品，進行細部硼濃度及硼同位素研究系統性工作等(微礦物鑽取粉末、酸鹼液溶解、樹栺分離及MCICP-MS, 本研究室新創硼同位素分析技術(Wang et al., 2015; Wang et al., 2020), 將可逐步解開寒武紀/前寒武紀過渡帶海水酸鹼值環境演化歷程及可能控制因素或成岩作用修正有初步掌控。 The Earth history and the evolution of life are closely interconnected. Changes in the ambient environment lead to selection of organisms best able to cope with the new settings. We have established an international-team, including scientists from China, Taiwan, Russia and USA to tackle various issues in Precambrian/Cambrian transition period. We have been assigned to focus on developing proper U-Pb dating technique for apatite grains or other authigenic minerals, as well as other redox sensitive isotopes in the Neoproterozoic Doushantuo and Lantian Formation, South China. These results will be published in a “PC-C Phosphogenic Event” special publications in a top-journal in this field in 2020, Precambrian Research (in press).This is a continuous of the “Precambrian/Cambrian Transition Zone Study”, we will examine in details of the phosphorites from the Doushantuo and Lantian Formation. Our preliminary SEM studies have documented the occurrence of numerous minerals suitable for U-Pb dating. Initial results using Electron Probe and LA-ICPMS analyses have also identified secondarily emplaced detrital minerals (e.g., zircon) that on the bases of their morphology and chemistry can be excluded from the micro-mineral age determinations. On the other hand, our studies will also focus step-by-step on environmental proxies, including B isotopes (for oceanic pH), S (for biogeochemical cycling), Mo-V-U (for redox and oxygenation conditions), Sr-Ca-Mg isotopes(for continental weathering), as well as stable C, N and O isotopes (for carbon sources and productivity). This year we will focus on our efforts to analyze various B and B isotopes in carbonates or phosphorites collected for a better understanding of the phosphorite specimens, in terms of the biogeochemical cycling of B and 11B recorded in the Neoproterozoic Doushantuo and Lantian Formation. A new sensitive MCICP-MC technique for B isotopic analyses, developed in our lab (Wang et al., 2012; Wang et al., 2020) will be applied to reconstruct marine pH environmental changes recorded in Lantian or Weng’an strata on the Snowball Earth. Our international team will use state-of-the-art techniques to provide new telling data about the evolution of life and the oceanic environment changes on the Snowball Earth period.